The implications of the 1984 amendment to the civil law act on quantum of damages / Muzafek Mohd Yusoff - Mohd Yusoff, Muzafek (Faculty of Law, 1986)
Anybody who has an had the duty of assessing damage: either the courts or outside then is fully aware of the difficulties with which that duty is beset. Quest— ion of liability are often difficult enough, but decision: of the courts over many years and the invaluable work of the textbook writers have provided a clear guide to the principles which govern liability. But it can never be possible to formulate any such clear guide in the assess— ment of damages, though certain principles have become clear enough. For each case depends upon its own peculiar and particular facts, and experience: has shown that the the fact: can Vary almost infinitely.